Comparative analysis between IFRS 9 and IPSAS 41 Financial Instruments - Martin Nikolov (Икономика и компютърни науки)
Abstract. The widespread use of IFRS accounting standards often creates the impression that financial reporting revolves solely around corporate interests and profit-driven entities. However, accounting standards are also essential in other sectors, particularly those serving public interests. This report aims to provide a brief overview of the public sector’s financial landscape and how accounting standards must be adapted to reflect its unique priorities and objectives. The difference between IFRS 9 and IPSAS 41 will be briefly discussed, highlighting key examples of their distinctions.